(3YWGjG GdNdGjG GdLPYjI (B:s (3bUI GdYde hGdjbjf (B/s - (3JTGf QG, LjhfLs; (3CHh GdjRjO, CTQa,s 1963- ((3GdbGgQI ;s (3OHj (B[(3GdEeGQGJ GdYQHjI GdeJMOI(B] :s (3efThQGJ HJGfI,s, 2019)
(3JcJTa ef NdGd gPG GdcJGH GdYLGFH GdeOgTI hQGA JUeje Gddg dLSe GdEfSGf hGdEecGfGJ ZjQ GdeMOhOI ddNdGjG GdLPYjI hSha JcJTa CjkVG Cfg HaVd GdJbOe GdePgd GdPj MbbJg eDSSI eYgO CHMGK GdNdGjG GdLPYjI (B"(3HjhSJGQ(B"(3, aj eLGd CHMGK GdNdGjG GdLPYjI GdeTJbI ef GdTMhe, GJNPJ GdHTQjI GdBf GdNWhI GdChdi fMh GdahR HMQHgG GdebOSI VO GdTjNhNI hGdeQV hdOjc HGdaYd hSjdI dEYGOI YbGQH GdSGYI Edi GdhQGA, hBed Cf jchf gPG GdcJGH eajOG dc, cNQjWI deSYGc cj JcJTagG HfaSc(B.s
(3ehLg Edi GdHGdZjf(B.s
Keywords: (3GdNdGjG GdLPYjIs -- (3GSJNOGe YdGLjs; (3Yde GdNdGjGs